Chopin pianist and teacher as seen by his pupils - Eigeldinger, Jean-Jacques (Cambridge Cambridge University Press, 1989)
The accounts of Chopin's pupils, acquaintances and contemporaries, together with his own writing, provide valuable insights into the musician's pianistic and stylistic practice, his teaching methods and his aesthetic beliefs. This unique collection of documents, edited and annotated by Jean-Jacques Eigeldinger, reveals Chopin as teacher and interpreter of his own music. Included in this study is extensive appendix material that presents annotated scores, and personal accounts of Chopin's playing by pupils, writers, and critics.
Keywords: Chopin, Frédéric -- 1810-1849; 19th Century (1801-1900); Instrumentalist; Piano; Education; Paris (France)